The 9-Item Physician Documentation Quality Instrument (PDQI-9) score is not useful in evaluating EMR (scribe) note quality in Emergency Medicine - Walker, Katherine J.; Wang, Andrew; Dunlop, William; Rodda, Hamish; Ben-Meir, Michael; Staples, Margaret (Applied Clinical Informatics, 2017)
Background: Scribes are assisting Emergency Physicians by writing their electronic clinical notes at the bedside during consultations. They increase physician productivity and improve their working conditions. The quality of Emergency scribe notes is unevaluated and important to determine.Objective: The primary objective of the study was to determine if the quality of Emergency Department scribe notes was equivalent to physician only notes, using the Physician Documentation Quality Instrument, Nine-item tool (PDQI-9).Methods: This was a retrospective, observational study comparing 110 scribed to 110 non-scribed Emergency Physician notes written at Cabrini Emergency Department, Australia. Consultations during a randomised controlled trial of scribe/doctor productivity in 2016 were used. Emergency physicians and nurses rated randomly selected, blinded and de-identified notes, 2 raters per note. Comparisons were made between paired scribed and unscribed notes and between raters of each note. Characteristics of individual raters were examined. The ability of the tool to discriminate between good and poor notes was tested.Results: The PDQI-9 tool has significant issues. Individual items had good internal consistency (Cronbach’s alpha=0.93), but there was very poor agreement between raters (Pearson’s r=0.07, p=0.270). There were substantial differences in PDQI-9 scores allocated by each rater, with some giving typically lower scores than others, F(25,206)=1.93, p=0.007. The tool was unable to distinguish good from poor notes, F(3,34)=1.15, p=0.342. There was no difference in PDQI-9 score between scribed and non-scribed notes.Conclusions: The PDQI-9 documentation quality tool did not demonstrate reliability or validity in evaluating Emergency Medicine consultation notes. We found no evidence that scribed notes were of poorer quality than non-scribed notes, however Emergency scribe note quality has not yet been determined.Citation: Walker KJ, Wang A, Dunlop W, Rodda H, Ben-Meir M, Staples M. The 9-Item Physician Documentation Quality Instrument (PDQI-9) score is not useful in evaluating EMR (scribe) note quality in Emergency Medicine. Appl Clin Inform 2017; 8: 981–993 https://doi.org/10.4338/ACI2017052017050080
Keywords: Clinical Documentation and Communications; Scribe; Emergency Medicine; Quality; Safety Culture